Working capital management performance in Air Asia, Malaysia Airlines and Qantas / Abu Thahir Abdul Nasser, Omar Samaf and Ahmad Marzuki Amiruddin Othman - Abdul Nasser, Abu Thahir; Samaf, Omar; Amiruddin Othman, Ahmad Marzuki (Research Management Institute (RMI), 2010)
The main purpose of this case study is to benchmark the working capital management performance (WCM) among Air Asia, Malaysia Airlines, and Qantas with an intention to identify the best practices in WCM to enhance operational efficiency in cash flow from operations. This case study is conducted by employing generic benchmarking among Air Asia a low cost airline, Malaysia Airlines and Qantas full service airlines, with an intention to provide valuable insights into operational efficiency and the pattern of current assets investment and financing policies adopted in the airline industry. "Cash conversion efficiency", a financial performance indicator is used to measure the operational efficiency, while "Days of working capital" a non financial performance indicator is used to identify the current assets investment and financing policies adopted in the firms studied. The findings of this study reveal that the low cost airline out performs the government and private owned full service airlines in the WCM. The government and private owned full service airlines studied do not have sufficient fund for their working capital requirement and the existing working capital in all the three airlines studied have not been utilized efficiently. This study also identifies an inverse relationship between the aggressive level of working capital financing and the cash conversion efficiency. Currently there is no available literature focusing exclusively on the WCM performance in the airline industry which may throw new light and facilitate the process ofimproving cash flow from operations and reducing the cost ofcapital. A better understanding ofthe WCMpractices in airline industry is especially beneficial because ofthe needfor efficient utilization ofthe working capital employed to achieve enhanced operational efficiency.